From Rivalry to Mutual Trust: The Othering Process between Bolivia and Chile - Leslie Wehner (German Institute of Global and Area Studies (GIGA), 2010)
Bolivia and Chile live in a culture of rivalry as a consequence of the Nitrate War (1879-1883). In each country's case, the construction of the other as a threat, a rival and/or inferior has shaped the discursive articulation of the bilateral relationship. Whereas the culture of rivalry is more evident in Bolivia because of its aspiration to alter the border, Chile's statusquo position, which stresses that there are no pending issues with Bolivia, as well as its construction of itself as superior, also represents rivalrous behavior. The perception of Chile as a threat and rival became especially evident in Bolivia during these two countries' bilateral negotiations to export gas to and through Chile (gas crisis from 2001-05). However, since Evo Morales and Michelle Bachelet took office in Bolivia (2006-present) and in Chile (2006-10), respectively, they have sought to change this culture of rivalry to one of friendship by constructing discursive articulations of self and other based on the principle of building mutual trust. Such a change in the form of othering is only possible to understand within the context of a crisis of meanings. The new approach of othering the counterpart as a friend has filled the void of meaning left by the crisis of discursive articulations of othering the counterpart as a rival, a threat and/or inferior. – – Bolivien und Chile leben - als Konsequenz des Salpeter-Krieges (1879-1883) - in einer 'Kultur der Rivalität'. Seit diesem Krieg wechseln sich in den bilateralen Beziehungen dieser beiden Länder Episoden der Anspannung mit Momenten relativer Beruhigung ab. Die Darstellung des jeweils Anderen als eine Bedrohung, als Rivale und die Einstufung als minderwertig hat die diskursive Umsetzung der bilateralen Beziehungen geformt. Während in Bolivien die 'Kultur der Rivalität' wegen der angestrebten Grenzänderung stärker in den Vordergrund rückt, nimmt Chile gegenwärtig eine Position ein, wonach es keine offenen Themen mit Bolivien gäbe. Jedoch zeugt die Betonung der chilenischen Seite als überlegene Kraft gegenüber Bolivien von offener Rivalität. Die Wahrnehmung Chiles als Bedrohung und als Rivale wurde in Bolivien während der Gas-Krise zwischen 2001 und 2005 offensichtlich. Seit dem Regierungsantritt von Evo Morales in Bolivien (2006-) und Michelle Bachelet in Chile (2006-2010) betonen beide, dass sie diese 'Kultur der Rivalität' beenden wollen und stattdessen eine diskursive Verständigung - basierend auf den Prinzipien der Freundschaft und des gegenseitigen Vertrauens - zwischen beiden Ländern anstreben.
Keywords: 300; discourse; othering; identity; crisis; change; Bolivia; Chile